A Bichromophoric Triazatruxene Tetrad as a Highly Tunable Multicolor Emitter and Its Application in OLEDs - Vogelsang, Lars; Haider, Muhammad Irfan; Vogelsang, Kai; Seewald, Tobias; Fakharuddin, Azhar; Bauch, Niklas; Maier, Gabriel; Deuter, Katharina L.; Birk, Tobias; Fonin, Mikhail; Schmidt-Mende, Lukas; Winter, Rainer F. (My University, 2025)
We report on the new star‐shaped triazatruxene (TAT) tetrad 1 , where three peripheral TAT moieties connect to a central TAT through propargylic spacers. The insulating nature of the linkers results in separate, partially overlapping blue and yellow‐orange emissions from the peripheral and central TATs. This renders 1 a multicolor emitter, whose emission color can be tuned by the choice of the excitation wavelength and the solvent. In frozen solution, dual fluorescence emission from the two different types of TATs is complemented by dual phosphorescence with radiative lifetimes in the range of seconds. Organic light‐emitting devices (OLEDs) constructed with 1 as the emissive layer achieved a peak irradiance of 5.87 µW/nm/m2 at 580 nm at an operation voltage of 6.7 V. Remarkably, the emission color of the electroluminescence can be varied from yellow over different hues of orange to red or even to near infrared (NIR) emission, depending on the applied voltage. Tetrad 1 is also redox‐active, indicating that 1 may simultaneously serve as a hole conductor and emitter. Its oxidized forms are panchromatic absorbers from the near UV to the NIR due to intra‐ and inter‐TAT charge‐transfer (CT) absorptions.
Keywords: 540